Pedotransfer Functions to Estimate Soil Water Retention Characteristics in Major Cotton Growing Shrink-swell Soils of Yavatmal District, Maharashtra - Bhaskar, S.K. Ray, Jagdish Prasad and S.V. Bobde, P.L.A. Satyavathi, P. Tiwary, B.P. (Journal of the Indian Society of Soil Science, 2018)
The shrink-swell soils of Yavatmal district, Maharashtra support rainfed cotton and production of crop is significantly affected by intermittent dry spells. Estimation of soil water retention characteristics of these soils is necessary in view of aberrant rainfall and irrigation scheduling. Based on easily measurable soil properties, Pedotransfer functions (PTFs) were developed and evaluated with the existing PTFs. The water retention characteristics of these soils are influenced by clay, CEC and ESP. The derived PTFs are able to accurately estimate water retention at 33, 300, 500, 800, 1200 and 1500 kPa, however the PTF for moisture content at 100 kPa did not performed well. The evaluation results indicate that the PTFs developed, in the present study, for shrink-swell soils perform better than the existing PTFs developed for other geographical regions for estimating the water retention characteristics of Yavatmal soils emphasizing the development of region-specific pedotransfer functions for estimating the water retention.